Embodiment in skateboarding videogames - Martin, Paul (Taylor & Francis Online (Routledge), 2013)
This article analyses the avatar in action games as both object of perception and instrument of action and perception. This allows for a picture to emerge of the way in which avatars in 3D action games serve as a kind of commentary on what it is to have a body in space. Two skateboarding games are analysed primarily through the lens of Martin Heidegger’s exposition of equipmentality in Being and Time. These skating games are chosen since they are examples of games which on the one hand provide spectacular images of the body in performance and on the other allow the player to feel in a heightened, focused and distorted way what it feels like to skate. By attending to the formal characteristics of the avatar as object of perception and instrument of perception and action and placing these within the context of the games’ different ideological positionings and assertions, it is possible to unpack some of the ways in which these games investigate embodiment as a culturally constituted phenomenon.